Pre Treatment Air Gambut Dengan Lempung Cengar Dan Penyisihan Zat Organik Dan Kekeruhan Dengan Membran Ultrafiltrasi Sistem Aliran Cross-Flow - Lasmita, Revi; Daud, Syarfi; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Water is an environment element that is needed to support all human life. Peat water is containing a Natural Organic matter (NOM) that make it brown, taste and smelling. Peat water quality not suitable with water quality standards Permenkes No. 416/MENKES/PER/IX/1990. One of the peat water treatment methods used in this study is pre treatment of coagulation-flocculation and ultrafiltration membrane. This study aims to determine the removal efficiency of organic matter and turbidity in the pre treatment of coagulation-flocculation using coagulants Cengar Clay, coagulants Cengar Clay to decrease organic matter and turbidity, determine the performance of membrane for flux and rejection of organic matter and turbidity with and without pre treatment of coagulation-flocculation, determine decrease of organic matter and turbidity in peat water treatment using ultrafiltration membrane with pre treatment of coagulation-flocculation. The highest removal efficiency in coagulation-flocculation for organic matter parameter and turbidity obtained at a dose of 100 ml with a variation efficiency value of 47,733% dan 70,484%. The highest flux ultrafiltration membrane with and without pre treatment of coagulation-flocculation obtained at a pressure of 1,5 bar. Rejection coefficient organic matter and high turbidity ultrafiltration membrane without pre treatment is obtained at a pressure of 0,5 bar respectively by 20,6% dan 96,9%. Rejection coefficient organic matter and high turbidity ultrafiltration membrane with pre treatment is obtained at a pressure of 0,5 bar respectively by 92% dan 100%. Decrease in organic matter and turbidity with the pre treatment of coagulation-floccultion and ultrafiltration membrane from 118,5 mg/l KMnO4 to 9,640 mg/l KMnO4 and 31 NTU to 0 NTU.Keywords: Cengar Clay, Coagulation-Flocculation, Peat Water, Ultrafiltration Membrane.